The Aesthetics of Allusion in the Qur’anic Discourse - An Analytical Study- - Mahmood Shakir AL-Jdayya , Assist. Prof. Dr. Haider (Basra studies journal, 2025)
The research is concerned with studying the aesthetics of allusion in the Qur’anic discourse, classifying it according to its type, analyzing it, and explaining it, in that it constitutes one of the basic building blocks of its structure, and is considered a main tool of its composition, and a means of its important means in the circle of communication and delivery, and influence and impact between the poles of the circle of reception; They are - the signifier and the signified, the target of the sign and the target of it - since there is no escape for any speech or text without their presence in its context, so the orator, speaker, speaker or writer cannot do without resorting to them, and seeking assistance in employing them, because they carry with their types and qualities of meanings and connotations. This is what the aesthetic analysis of the mechanisms of modern criticism and text linguistics has focused on in revealing the aesthetic bonds of two central signs that support each other in the coherence and strength of the speech, and in the harmony of directing and linking its context and in the manner of introducing an important element of the elements that form its aesthetics. The first is concerned with clarifying the contrastive opposition, and the second works on the depth of the agreement of meaning and its confirmation, and each one has its intended role in the aim and purpose of the speech. .